Effect of the inoculation of native arbuscular mycorrhizal fungi and one selected species on the Brachiaria decumbens cv Basilisk and Panicum maximun cv. Mombaza pastures - Crespo Flores, G.; Gonz?lez, P. J.; Arzola, J.; Morgan, O. (Cuban Journal of Agricultural Science, 2010)
In a completely randomized design with factorial fit and five repetitions, the effect of the inoculation of native arbuscular mycorrhizal fungi (AMF) and one species (Glomus hoi-like) of AMF selected from the mycorrhizal structures were evaluated, as well as the content of NPK in the aerial biomass, and the growth and yield of dry matter (DM) of the Brachiaria decumbens cv Basilisk and Panicum maximun cv. Mombaza pastures. Also, the efficiency index (EI) of the AMF and their participation in pasture nutrition were determined. The trial was conducted in pots with lixiviated red ferrallitic soil from the plots cultivated with both pasture species for five years. The native AMF were collected out of them. There were interactions (P < 0.01) between the AMF and the pasture species for the indicators under study. With the inoculation of G. hoi-like, the highest percentages of mycorrhizal colonization (67.22 and 42.76 %) and visual density (2.63 and 1.92 %) were obtained, as well as the highest density of spores (108 and 70 spores/50g of soil), height (24.94 and 21.43 cm) and yield of pastures (29.85 and 25.93 g of DM pot-1). The highest values of these variables were observed in B. decumbens. Likewise, G. hoi-like showed higher EI than that of the native AMF and it also had higher participation in the nutrition of the pastures. It is concluded that, in the conditions of the trial, G. hoi-like was more efficient than the native AMF to enhance the growth of the pastures. The effectiveness was higher in B. decumbens and it was related to higher development of the mycorrhizal structures and to the higher participation in pasture nutrition. It is recommended to test in field conditions the effect of inoculation of Glomus hoi-like in similar pasture species and soil types, as well as to evaluate the efficiency of the native AMF and the new selected species of AMF in other grassland conditions. Key words: arbuscular mycorrhizal fungi, Brachiaria decumbens, Panicum maximun.